Asia-Pacific. Issue 4 (4th July 2022) - Xiang, Lanxin
Abstract : The Avoidable War: The Dangers of a Catastrophic Conflict Between the US and Xi Jinping's China Kevin Rudd. New York: PublicAffairs, 2022. 32.00. 432 pp. Line of Advantage: Japan's Grand Strategy in the Era of Abe Shinzo Michael J. Green. New York: Columbia University Press, 2022. £28.00/35.00. 328 pp. Crisis Narratives, Institutional Change, and the Transformation of the Japanese State Sebastian Maslow and Christian Wirth, eds. Albany, NY: SUNY Press, 2021. 95.00. 344 pp. The Sovereign Trickster: Death and Laughter in the Age of Duterte Vicente L. Rafael. Durham, NC: Duke University Press, 2022. 24.95. 192 pp. China vs America: A Warning Oliver Letwin. London: Biteback Publishing, 2021. £20.00. 288 pp.